2011
DOI: 10.1111/j.1470-6431.2011.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption patterns and healthy eating across the household life cycle in Hungary

Abstract: The family or household life‐cycle concept has a significant place in the consumer behaviour literature. The ideology reflects the different lifestyle, income and expenditure patterns brought about by family‐form transitions. The household life‐cycle model is accepted as a predictive tool of household expenditures; however, this predictive ability is debated. The different life‐cycle stages may also have an affect on dietary habits and health consciousness. Several studies supported that the family form has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
3
25
0
1
Order By: Relevance
“…Most of previous research highlighted the effect of family income on food habits. Specifically, high-income families adopt a healthier diet, characterized by a high intake of fruit, vegetables, fish, and dairy products; further, they prefer-for their children-foods rich in protein, polyunsaturated fats, folic acid, calcium, and iron (Neulinger and Simon 2011). Conversely, low-income families consume, in large amount, meat products, whole milk, fats, sugars, potatoes, and cereals, while the consumption of fruit and vegetables is smaller (Patrick and Nicklas 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of previous research highlighted the effect of family income on food habits. Specifically, high-income families adopt a healthier diet, characterized by a high intake of fruit, vegetables, fish, and dairy products; further, they prefer-for their children-foods rich in protein, polyunsaturated fats, folic acid, calcium, and iron (Neulinger and Simon 2011). Conversely, low-income families consume, in large amount, meat products, whole milk, fats, sugars, potatoes, and cereals, while the consumption of fruit and vegetables is smaller (Patrick and Nicklas 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Participation in a CSA community may significantly change the food shopping habits of the primary food shopper of the family, and also often impacts on the food consumption of the whole household (Kis, 2014;Russell & Zepeda, 2008;Thompson & Coskuner-Balli, 2007). It is evident that the family has a strong effect on individuals' healthy eating, sustainable consumption or eating local (Bingen et al, 2011;Neulinger & Simon, 2011;Salazar, Oerlemans, & Stroe-Biezen, 2013). Not surprisingly, family involvement in food preparation, shared approaches in regard to CSA vegetables use among participants, and family members are important elements of experiences of belonging to a CSA (Uribe et al, 2012;Wharton et al, 2015).…”
Section: Theore Ti C Al Backg Roundmentioning
confidence: 99%
“…They found that male household members place greater demands on household food supplies than female members. In summary, household size, employment status, marital status, gender, region of living and other several demographic characteristics also influence the level of food spending due to the differences in their roles and preferences within the household (Nayga 1995;Teklu 1996;Jae et al 2000;Mihalopoulos and Demoussis 2001;Oygard 2000;Sabates et al 2001;Hossain 2002;Kirkpatrick and Tarasuk 2003;Thiele and Weiss 2003;Guest et al 2006;Ricciuto et al 2006;Moss et al 2007;García and Grande 2010;Jacobson et al 2010;Neulinger and Simon 2011;Barigozzi et al 2012;Tekguc 2012;Liu et al 2013;Kostakis 2014;Humphries et al 2017;Marques et al 2018).…”
Section: A Brief Literature Review On Food Behaviormentioning
confidence: 99%